Ancient Jewish Inscriptions in Venetian Religious Painting of Renaissance - Chechik, Liya A. (Actual Problems of Theory and History of Art, 2013)
In the following article we shall study a variety of Hebrew inscriptions incorporated into Venetian religious painting of the Renaissance, including the masterpieces by Vittore Carpaccio, Cima da Conegliano, Jacopo de’Barbari, Rocco Marconi and others. The emergence of Hebrew inscriptions reflected a distinct desire for authenticity in the Renaissance mentality. However, it is obvious that the meaning of Jewish inscriptions was unclear to a common Christian “public”. Jewish type or imitation of Adamic script (when the latent symbolic sense could be read as an artistic image) were deliberately employed in paintings, possibly in an attempt to resurrect a prophetic quest of the Old Testament. However, it is obvious that the presence of Jewish type (inscriptions) or imitation of Adamic script (when the latent symbolic sense could be read as an artistic image), created an aura of an old message, making recall the prophetic mission of lines of the Old Testament.
Keywords: Hebrew inscriptions; painting; Renaissance art; Venice; Vittore Carpaccio; Rocco Marconi; Cima de Conegliano; Jacopo de Barbari